PENGARUH GAYA KEPEMIMPINAN, KOMPENSASI FINANSIAL, DAN IKLIM ORGANISASI TERHADAP MOTIVASI KERJA KARYAWAN NEW KUTA GOLF - Dewi, Putu Evi Rosalinda; Surya, Ida Bagus Ketut (E-Jurnal Manajemen; Vol 11 No 4 (2022)DO - 10.24843/EJMUNUD.2022.v11.i04.p08, 2022)
The purpose of this study was to determine the effect of leadership style, financial compensation and organizational climate on employee motivation at New Kuta Golf Bali. The sample used was 62 employees, with proportional random sampling method. The method of data collection was done through interviews and questionnaires. The analysis technique used is multiple linear regression. The results of the analysis found that: 1) Leadership style had a positive and significant effect on employee motivation at New Kuta Golf Bali; 2) Financial compensation has a positive effect on employee work motivation; 3) Organizational climate also has a positive effect on employee motivation. Keyword: leadership style; financial compensation; organizational climate; work motivation.